Attitude Towards Improving the Level of Living Among Rural Malays in Two Villages of Kubang Pasu District - Bakar, Habshah (1989)
The primary objective of this study was to explore the attitude towards improving the level of living among the rural Malays, in two villages of the Kubang Pas u district. The specific objectives were: a) to analyze the relationship between selected socio - demographic variables and the attitude towards improving the level of living, and b) to identify the profiles of those with positive attitude towards improving their level of living. The data collected from 120 male he ads of households revealed that their attitudes cores towards improving the level of living was average. This was manifested by their average exposure towards change agents, high aspiration to improve their lives and an average score on the Internal - External Locus of Control scale.